No Gender Difference in Foreign Medical Students' Hematology Clerkship. (13th March 2018) - Li, Qing; Chen, Jianhui; Wan, Bo; Li, Xiaofan
Abstract : Hematology is a difficult aspect of medicine for students to learn. Students need hematology clerkship training to develop their clinical skills. The influence of gender on different teaching methods and performance in foreign medical students is still unknown, especially in hematology clerkship. To address this issue, we tested performance differences between foreign male and female students in clinical practice. Twenty-two foreign medical students attended a two-week hematology clerkship in Fujian Medical University Union Hospital. The lecture-based learning (LBL) method and mixed team-based learning (MTBL) method were used in hematology clerkship. Eight foreign students were assigned to LBL group, and fourteen foreign medical students were assigned to MTBL group. Our previous work found that MTBL methods benefit both foreign medical students and Chinese postgraduates. In this study, practice scores and case-writing scores were analyzed between boys and girls. The results showed that the mean of scores in practice test scores and case writing scores was not significantly different between genders (P > 0.05 ), as well as subgroup analysis in LBL and MTBL groups (P > 0.05 ). This study indicated that practice test scores and case-writing scores in hematology clerkship were the same between boys and girls, which were not related to teaching methods. This study also indicated that both genders can benefit from the new MTBL teaching methods.